Activation of spleen tyrosine kinase (Syk) at fertilization in Rhinella arenarum eggs - Mouguelar, Valeria Soraya (2014)
Recently, we have provided evidence for the involvement of a cytosolic tyrosine–phosphorylatable 70 kDa oocyte protein in Rhinella arenarum (Anura: Bufonidae) fertilization. The aim of the present work was to characterize its phosphorylation, determine the identity of this protein and establish its biological role during the fertilization process. Tyrosine phosphorylation of the 70 kDa protein was not observed in eggs activated with the calcium ionophore A23187. Pretreatment of oocytes with the tyrosine kinase inhibitor genistein effectively blocked the fertilization-dependent phosphorylation of the 70 kDa protein. In order to identify this protein, we examined the presence in amphibian oocytes of non-receptor 70 kDa tyrosine kinase members of the Syk/Zap70 and Tec families by RT-PCR using degenerate primers. We found that R. arenarum oocytes contain the transcripts coding for Syk and Tec kinases. Western blot analysis confirmed the presence of Syk protein in unfertilized oocytes and eggs. Studies using phospho-Syk specific antibodies showed that fertilization rapidly (less than 10 minutes) induces phosphorylation on Syk tyrosine residues (352 and 525/526) that are necessary for the activation of the enzyme. Finally, specific inhibition of Syk with the R406 compound provoked a diminished fertilization score, thereby confirming a functional role of the Syk protein during R. arenarum fertilization. To our knowledge this is the first time that Syk is described as a player in the signaling cascade activated after fertilization.